تجلّيات الرّمز في نصوص سعد الله ونّوس المسرحيّة / 1990-1997 / (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تهدف هذه الدّراسة إلى الكشف عن تجلّيات الرّمز في نصوص سعد الله ونّوس المسرحيّة، وطبيعة هذه الرّموز، وسبب توظيفها، ومدى اندماجها، واتّصالها بالرّؤيا الفكريّة والجماليّة التي تقدّمها تجربته في هذه النّصوص يضاف إلى ذلك الكشف عن دورها كعنصر جماليّ مشكّل في هذه التّجربة. وتعدّدت الرّموز في مسرحه بين دينيّة وتاريخيّة وأسطوريّة وتراثية وأدبية. وقد وقع الاختيار على التّسعينيّات لأنّ هذه الحقبة، بإجماع النّقاد جميعاً، كانت الأكثر خصوبةً وعطاءً من قبل الأديب؛ لأنّ تجربته بلغت أوج نضجها في هذه المرحلة. This study aims to detect embodiments of the symbol in Saad Allaa Wannuos,s dramatic text, the nature of the symbol, the goal of using it, and how far it fits and relate to the  intellectual and aesthetic vision presented through his experience in  these texts. In addition to this, the study tries to detect the role of the symbol as constructive  esthetic element in this experience. The symbols in Wannuos,s Dramatic Text are religious, historical, mythological, literary and literary heritage ones. The nineties has been chosen in this study since all critics agree that it is the most fertile and generous era of the writer career for his experience reaches its maximum   maturity durinig this stage.